Asperger syndrome : assessing and treating high-functioning autism spectrum disorders - McPartland, James C.; Klin, Ami; Volkmar, Fred R (New York: The Guilford press, 2014)
"Completely revised with the latest research and clinical strategies, this is the authoritative volume on Asperger syndrome (now part of DSM-5 autism spectrum disorder). Considered the definitive reference since its initial publication, the book focuses on how to assess each child or adolescent's needs and provide effective interventions in the areas of communication, behavior, and academic and vocational functioning. The neural and genetic bases of autism spectrum disorders are also explored. New to This Edition *Expanded coverage of evidence-based assessment and treatment, including two chapters on behavioral interventions. *Addresses challenges in the transition to new diagnostic criteria for autism spectrum disorder in DSM-5. *Chapters on neuropsychological advances, the transition to higher education, and forensic issues. *Many new authors and extensively revised chapters. "--
"Subject Areas/Keywords: adolescents, adults, AS/HFA, ASD, Asperger syndrome, assessments, autism spectrum disorders, behavioral, children, communication, developmental disabilities, diagnosis, DSM-V, DSM-5, genetics, high-functioning, interventions, neuropsychology, PDD-NOS, pervasive developmental disorders, psychopharmacological, social competence, social skills training, treatments Description: Completely revised with the latest research and clinical strategies, this is the authoritative volume on Asperger syndrome (now part of DSM-5 autism spectrum disorder). Considered the definitive reference since its initial publication, the book focuses on how to assess each child or adolescent's needs and provide effective interventions in the areas of communication, behavior, and academic and vocational functioning. The neural and genetic bases of autism spectrum disorders are also explored. "--
Machine generated contents note: 1. Asperger Syndrome: An Overview, Fred R. Volkmar, Ami Klin, and James McPartland -- 2. Evidence-Based Assessment of Asperger Syndrome: A Selective Review of Screening and Diagnostic Instruments, Jonathan M. Campbell, Carrah L. James, and Sarah F. Vess -- 3. Neuropsychological Characteristics of Asperger Syndrome, Katherine D. Tsatsanis -- 4. Communication in Asperger Syndrome, Rhea Paul, Rebecca Landa, and Elizabeth Simmons -- 5. Treatment and Intervention Guidelines for Asperger Syndrome, Fred R. Volkmar, Ami Klin, and James McPartland -- 6. Addressing Social Communication in Asperger Syndrome: Implementing Individualized Supports -- across Social Partners and Contexts, Emily Rubin -- 7. Behavioral Treatments for Asperger Syndrome, Brenda Smith Myles, Kai-Chien Tien, Hyo Jung Lee, Yu-Chi Chou, and Sheila M. Smith -- 8. Frameworks for Behavioral Interventions to Improve Peer Relationships and the Management of -- Emotions in Asperger Syndrome, Tony Attwood -- 9. Psychopharmacological Treatment of Asperger Syndrome, Alexander Westphal, Dana Kober, Avery Voos, and Fred R. Volkmar -- 10. Asperger Syndrome in Adolescence and Adulthood, Michael D. Powers and James W. Loomis -- 11. Transition to Higher Education for Students with Autism Spectrum Disorder, Jane Thierfeld Brown and Lorraine Wolf -- 12. Asperger Syndrome and Forensic Issues, Marc Woodbury-Smith -- 13. Social Brain Function and Its Development: New Insights into Autism Spectrum Disorders, Kevin A. Pelphrey, Brent C. Vander Wyk, Sarah Shultz, and Caitlin M. Hudac -- 14. Genetics of Asperger Syndrome, Susan E. Folstein.
Includes bibliographical references and index.
Keywords: Asperger's syndrome; PSYCHOLOGY / Psychotherapy / Child & Adolescent; MEDICAL / Psychiatry / Child & Adolescent; SOCIAL SCIENCE / Social Work; EDUCATION / Special Education / General; MEDICAL / Audiology & Speech Pathology; PSYCHOLOGY / Neuropsychology